Efficacy and safety of camrelizumab plus transarterial chemoembolization in intermediate to advanced hepatocellular carcinoma patients: A prospective, multi-center, real-world study - You, Ran; Xu, Qingyu; Wang, Qi; Zhang, Qingqiao; Zhou, Weizhong; Cao, Chi; Huang, Xiangzhong; Ji, Honghai; Lv, Penghua; Jiang, Hao; Lu, You; Jin, Yong; et al. (Frontiers in Oncology, 2022)
Objective Camrelizumab is a newly developed program-death receptor one inhibitor; the real-world evidence about its application in hepatocellular carcinoma (HCC) treatment is lacking. Therefore, this prospective, multi-center, real-world study evaluated the efficacy and safety of camrelizumab plus transarterial chemoembolization (TACE) in treating intermediate-to-advanced HCC patients. Methods This study consecutively enrolled 101 intermediate to advanced HCC patients. All patients received camrelizumab-based treatment within 30 days of the perioperative period of the TACE operation. The primary outcome was progression-free survival (PFS), and the secondary effects were overall survival (OS), objective response rate (ORR), disease control rate (DCR), and AEs. Results Specifically, the median PFS was 9.7 (95% confidence interval: 7.4–12.0) months, with a 1-year PFS rate of 30.6%. Meanwhile, the median OS was not reached (NR) yet, with a 1-year OS rate of 61.9%. Besides, the CR, PR, SD, and PD rates were 12.8%, 44.9%, 29.5%, and 12.8%, respectively. The ORR and DCR were 57.7% and 87.2%, respectively. More cycles of camrelizumab were independently correlated with prolonged PFS (hazard ratio (HR): 0.415, P = 0.002), whereas longer intervals between camrelizumab administration and TACE were independently associated with unfavorable PFS (HR: 1.873, P = 0.032). The incidence of total AEs was 90.1%; most AEs were grade 1 (20.8%), grade 2 (28.7%) and grade 3 (37.6%), while only 3 (3.0%) patients had grade 4 AEs. Conclusion The camrelizumab plus TACE regimen is effective and safe, indicating its potential to serve as a promising treatment choice for intermediate to advanced HCC patients.